A Selective Study: Camels Analysis of Indian Private Sector Banks - Dudhe, C. (International Journal of Engineering and Management Sciences, 2018)
Banking sector is one of the fastest growing sectors in India. Today’s banking sector becoming more complex. Evaluating Indian banking sector is not an easy task. There are so many factors, which need to be taken care while differentiating good banks from bad ones. Performance evaluation of the banking sector is an effective measure and indicator to check the soundness of economic activities of an economy. The contribution of RBI and other policy maker, the banking industry has witnessed regulatory requirements like BASEL III norms. These regulatory changes have influenced prominent improvement in efficiency and performance of the Indian Scheduled Commercial Banks in the past few years. In the present study an attempt was made to evaluate the performance & financial soundness of select Private Sector Banks like ICICI,HDFC AND YES bank using CAMEL approach from 2013 to 2017 as well one way anova method. It is observed that on an average ICICI was at the top most position. It is also observed that yes Bank was at the bottom most position in selected CAMEL ratios.